Colonic Mucormycosis In A Post Covid Patient: A Case Report - Patkar, Amrita; Kalwadia, Neha; Dadhich, Shailja; Potdar, Ojas; Mulchandani, Manoj (Journal of Society of Surgeons of Nepal, 2023)
Mucormycosis is rare infection caused by fungi of order Mucorales which frequently involves rhino-cerebral or respiratory system with involvement of gastrointestinal (GI) tract being rare. Classically majority of patients with invasive mucormycosis are immunocompromised and/or have poor glycemic control. This happens especially during recovery phase of COVID-19 when patients are immunocompromised and simultaneously having poor glycemic control. While gastrointestinal (GI) mucormycosis is rare, stomach and colon are most commonly affected organs, and mortality can be as high as 85%. Diagnosis is difficult since signs and symptoms, imaging and intraoperative gross appearance may not suggest mucormycosis. Diagnosis is usually by histopathologic identification of fungal hyphae in biopsy specimen. A high index of suspicion is therefore necessary in post-COVID-19 patients presenting with mesenteric ischemia or bowel perforation especially if they were immunocompromised. Here we present a case of post COVID disseminated mucormycosis in a 59-year-old diabetic male patient.